Grow-out culture of oyster Magallana bilineata (Röding, 1798) using pouches A comparison of growth and survival in the river and earthen pond - Lebata-Ramos, Ma. Junemie Hazel L.; Solis, Ellen Flor D.; Almeida, Mark Jude C. (2023)
Oysters are among the most in-demand aquaculture commodities in the Philippines and worldwide. With the decreasing culture area and the deteriorating water quality of oyster beds, there is a need to explore new culture sites and techniques to address the problems of dwindling stocks and the increasing demand for better quality oysters. This study compared the growth and survival of the oysters Magallana bilineata, the new accepted name of Crassostrea iredalei, cultured in an earthen pond and the river using pouches suspended from rafts. Mean growth rates of oysters in length and weight were significantly higher in those reared in the river (0.56 ± 0.02 cm mo-1; 10.27 ± 0.42 g mo-1) than those in the pond (0.41 ± 0.03 cm mo-1; 5.99 ± 0.22 g mo-1), but the meat yield of oysters reared in the river (25.96 ± 0.92%) was almost the same as in the pond (24.05 ± 1.41%). Likewise, the proximate composition was the same for oysters coming from the river and the pond, respectively — 58.04 ± 0.14% and 53.86 ± 0.38% crude protein, 7.00 ± 0.08% and 7.93 ± 0.38% crude fat, 24.68 ± 0.07% and 28.54 ± 0.74% nitrogen-free extract, and 10.27 ± 0.01% and 9.68 ± 0.01% ash. Oyster survival at harvest was significantly higher in the river (70.21 ± 2.84%) than in the pond (13.10 ± 1.57%). However, with some interventions, ponds may still be utilized for oyster culture despite the low survival results in this study. Extending oyster culture in these aquaculture facilities may serve as a basis for interventions to make the pond more habitable for oysters and may help boost production in the country.
Keywords: Oyster culture